Open Public Transport Data in Macedonia - Jovanovik, Milos; Trajanov, Dimitar; Najdenov, Bojan; Mishevska, Elena (Faculty of Computer Science & Engineering, Skopje, 2014)
The need to represent data on the Web in a way that will make it easier to manage, has led to new solutions for data representation, visualization, storage and querying. The concepts of Open Data, Linked Data and the Semantic Web offer a significant improvement in information and data dissemination. These concepts aim towards making data on the Web machine-readable and enable interlinking between data from different datasets, published on different locations. This allows easier data retrieval by software agents, and enables use-case scenarios which are unavailable over isolated data silos. On the other hand, personal time management and daily commute navigation in urban areas are one of the biggest influencers on the quality of life of a person. Public transport data has high value for citizens and generates numerous use-cases. In this paper, we describe the process of obtaining data from the public transport company JSP Skopje, transforming them into the standardized Google Transit Feed Specification1 format, enhancing them and creating 4 star Open Data. We reused the Transit Ontology2 and the W3C Geospatial Vocabulary3, and developed our own complementing ontology for annotation purposes. We published the generated RDF datasets in order to support the provided use-case scenarios from this domain via a public SPARQL endpoint.
Keywords: Public Transport; Open Data; GTFS; RDF; Ontologies